Evolutionary patterns of structural disorder and post-translational modifications in the 18.5 kDa myelin basic protein - KOSZORUS, Ilka; KÓSA, Ferencz (Studia Universitatis Babeș-Bolyai Biologia, 2025)
Myelin basic protein (MBP, 18.5 kDa isoform) is a key structural component of the myelin sheath, where it drives multilayer compaction through electrostatic interactions and dynamic conformational transitions. Despite its functional importance, a comprehensive understanding of MBP’s evolutionary patterns of intrinsic disorder, post-translational modifications (PTMs), and sequence-derived properties across vertebrates have been lacking. Here, we analyzed MBP consensus sequences from six major vertebrate clades (Chondrichthyes, Teleostei, Amphibia, Reptilia, Aves, Mammalia) using an integrated bioinformatic framework combining intrinsic disorder predictions, Shannon entropy-based complexity profiling, hydrophobic moment (μH) analyses, net charge per residue (NCPR) patterns, and experimentally supported PTM mapping. Our results reveal that MBP maintains a highly conserved intrinsically disordered architecture characterized by long N- and C-terminal IDRs and several clade-specific central IDRs. Teleosts exhibit a truncated N-terminal, lacking the first 15 residues, but compensate through additional positively charged residues downstream, preserving membrane-binding potential. Amphibians show unique insertions enriched in basic residues, leading to the longest MBPs and potentially enhanced lipid interactions. Shannon entropy and μH profiles demonstrate alternating conserved α-helices and flexible IDRs that overlap with PTM hotspots, particularly phosphorylation and citrullination sites, suggesting dynamic regulatory roles. NCPR analyses highlight a conserved electrostatic topology composed of alternating basic clusters and acidic/neutral dips, balancing reversible membrane adhesion with controlled aggregation. Together, these findings demonstrate that MBP combines strong structural conservation with lineage-specific adaptations in intrinsic disorder, charge distribution, and PTM patterning. This evolutionary flexibility likely underpins MBP’s ability to support functional diversity in myelin architecture while maintaining its essential role in vertebrate nervous system evolution. Article history: Received 31 August 2025; Revised 4 December 2025; Accepted 05 December 2025; Available online 20 December 2025